Implementasi Coretax Pada KPP Pratama Lamongan - Friska Dini Margareta; Yasfina Qurrota Ayun; Guruh Marhaenis Handoko Putro (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2026)
This study aims to analyze and explain how the implementation of the Core Tax Administration System (Coretax) affects the operational performance of tax authorities (fiskus) as primary users, as well as to identify the benefits and technical obstacles that emerged during the full implementation phase as of January 2025. This in-depth exploration was evaluated using the DeLone & McLean Information Systems Success Model (ISSM) framework. The research applied a qualitative method with a case study approach at KPP Pratama Lamongan, under the Regional Office of DJP East Java II. Data were gathered through a triangulation method combining in-depth interviews with three tax officers, direct observation, and documentation analysis. The results indicate that Coretax has successfully transformed tax administration into an integrated single platform, particularly through the Registration Module and Case Management Module. Coretax excels in system and information quality with real-time data updates. However, post-implementation evaluation revealed fluctuating user satisfaction at around 70% due to national technical challenges, including data anomalies after migration, system errors following a refresh action, and high interface complexity. Furthermore, these integration benefits have not yet directly improved the achievement of Key Performance Indicators (KPI/IKU) because the energy of the tax officers was heavily consumed by adapting to new procedures and managing dual roles as system users and taxpayers' facilitators during this transition phase. Keywords: Coretax, Tax Authority Performance, DeLone & McLean ISSM, Tax Administration System, Case Study.